Do crude oil prices spillover food prices? evidence for Asia and Pacific countries - Alom, Fardous (Inderscience Publishers, 2015)
This study investigates the mean and volatility spillover effects of world crude oil prices on the food prices for selected Asia and Pacific countries employing vector autoregression (VAR) and generalised autoregressive conditional heteroskedasticity (GARCH)-family models over 2 January 1995 to 30 April 2010. The findings suggest that the oil prices positively influence food prices of the selected countries both in mean and in volatility. Stronger mean and volatility spillover effects are found for the recent subsample period suggesting increasing interdependence between world crude oil and Asia-Pacific food markets in recent times. In terms of mean spillover effects net food importer countries’ food price show stronger effects to the shocks, whereas in terms of volatility spillover effects no distinction in absorbing the oil price shocks can be made between exporters and importers. The findings recommend that crude oil prices should be taken into consideration in policy preparation and forecasting purposes for food prices.